Calendar Festivals as a Form of Transnationalism and Cultural Strategy in the Mixed Finnish-Lithuanian and Greek-Lithuanian Families - Motuzaite Akvile (ELM Scolarly Press, 2022)
Abstract: The object of the paper is to research the celebration of calendar
festivals within Finnish-Lithuanian and Greek-Lithuanian families in Finland
and Greece respectively. The subject was approached mainly from the
Lithuanian women’s perspective, since most of the mixed marriages involved
Lithuanian females and rarely Lithuanian men in the countries chosen.
Six main Lithuanian calendar festivals of different origins were in focus of
the study. Three festivals belong to the Christian calendar: Christmas Eve
(Kūčios), Christmas (Šv. Kalėdos) and Easter Day (Šv. Velykos); and the other
three are national festivals significant for the State of Lithuania historically:
16th February (Day of Reinstating of the State of Lithuania), 11th March (Day
of the Re-Establishment of the State of Lithuania) and 6th July (Statehood
Day). The aim of the research is to reveal how the calendar festivals referred
to above are celebrated in the particular context of emigration: within mixed
marriages. Available transnational connections suggest different forms of
celebrating, which are shaped following certain strategies.
Keywords: calendar festivals, cultural strategy, identity, mixed marriage
transnationalism